European Archives of Paediatric Dentistry - Toumba, Jack.; Lygidakis, Nick.; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
The aim and scope of European Archives of Paediatric Dentistry (EAPD) is to promote research in all aspects of dentistry for children, including interceptive orthodontics and studies on children and young adults with special needs. The EAPD focuses on the publication and critical evaluation of clinical and basic science research related to children. The EAPD will consider clinical case series reports, followed by the relevant literature review, only where there are new and important findings of interest to Paediatric Dentistry and where details of techniques or treatment carried out and the success of such approaches are given.
Keywords: Dentistry; Dentistry